Potential Factors of Primary Hospital Healthcare Professionals in Hindering the Abolition of Routine Skin Test for Cephalosporin: A Cross-Sectional Study - Li B; Jiang L; Wu N; Chen Y; Xu Z; Xu F; Chen H; Liu T (Dove Medical Press, 2023)
Bo Li,1,2 Li Jiang,1,2 Ni Wu,1,2 Yao Chen,1,2 Zhi Xu,3 Fengcheng Xu,2,4 Heping Chen,1 Tianhu Liu2,4 1Clinical Pharmacy Department, The Third Affiliated Hospital of Chengdu Medical College, Pidu District People's Hospital, Chengdu, Sichuan, People's Republic of China; 2Drug Clinical Trial Management Center, The Third Affiliated Hospital of Chengdu Medical College, Pidu District People's Hospital, Chengdu, Sichuan, People's Republic of China; 3Department of Respiratory and Critical Care Medicine, The Third Affiliated Hospital of Chengdu Medical College, Pidu District People's Hospital, Chengdu, Sichuan, People's Republic of China; 4Department of Cardiovascular Medicine, The Third Affiliated Hospital of Chengdu Medical College, Pidu District People's Hospital, Chengdu, Sichuan, People's Republic of ChinaCorrespondence: Bo Li, Clinical Pharmacy Department, The Third Affiliated Hospital of Chengdu Medical College, Pidu District People's Hospital, Chengdu, Sichuan, People's Republic of China, Email lbydcg@163.com Tianhu Liu, Department of Cardiovascular Medicine, The Third Affiliated Hospital of Chengdu Medical College, Pidu District People's Hospital, Chengdu, Sichuan, People's Republic of China, Email lthzgl@163.comBackground: In 2021, National Health Commission of the People's Republic of Chinese issued a document that no longer recommended the routine skin test for cephalosporin (RSTC). However, there is still resistance to the cancellation of RSTC in a primary hospital. The study aimed to explore the potential factors for hindering the abolition of the RSTC in a county-level hospital based on the PRECEDE model.Methods: The cross-sectional study was conducted on healthcare workers in the Pidu District People's Hospital, Chengdu, by online questionnaire from September 10 to September 25 in the 2021.The PRECEDE model was used to divide the potential factors of healthcare professionals in hindering the abolition of the RSTC into predisposing factors, enabling factors and reinforcing factors. Data were analyzed by ANOVA, Chi-square test, multiple linear and multiple logistic regression analysis.Results: We collected 605 respondents' valid questionnaires. 254 healthcare professionals were against cancellation of the RSTC, accounting for 41.98%. Multiple linear regression analysis showed that working for 6~10 years (β = 1.953, P = 0.024), medium (β = 1.995, P = 0.030) or senior (β = 4.003, P = 0.007) professional qualification, pharmacists (β = 3.830, P = 0.013) and working in surgical department (β= 4.462, P < 0.001) were significantly associated with higher score of predisposing factors, enabling factors, and reinforcing factors on abolition of RSTC. Furthermore, multiple logistic regression analysis showed that pharmacists (OR=3.113, 95% CI: 1.341- 7.223, P=0.030), medium professional qualification (OR=1.272, 95% CI: 0.702- 2.302, P=0.008), scores of predisposing factors (OR=1.335, 95% CI: 1.033- 1.726, P=0.009), and scores of enabling factors (OR=1.208, 95% CI: 1.109- 1.315, P< 0.001) were independently associated with the positive anticipated behavior on the abolition of RSTC. While nurses (OR=0.516, 95% CI: 0.284- 0.938, P< 0.001) were independently associated with anticipated negative behavior.Conclusion: Pharmacists, medium professional qualification, and healthcare professionals with higher scores of predisposing and enabling factors were more likely to have a positive anticipated behavior on the abolition of RSTC, while nurses did not.Keywords: cephalosporin, skin test, potential factors, PRECEDE model, cross-sectional study